THE EFFECT OF USE OF MOBILE BANKING, INTERNET BANKING AND CREDIT RATIO ON THE VALUE OF BANKING COMPANIES - Sarah Yuliarini; Monica Safira Sugiharto (Journal of Artificial Intelligence and Digital Economy, 2024)
This research aims to determine the influence of the use of mobile banking and internet banking as well as the credit ratio on the value of banking companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. This research uses the dependent variable company value proxied by price to book value (PBV) and the independent variables mobile banking and internet banking as well as the credit ratio proxied by non-performing loans (NPL). The design of this research is quantitative research with a descriptive approach. Based on sampling using purposive sampling, the number of banks in Indonesia is 40 banks and a sample of seven banking sector companies listed on the Indonesia Stock Exchange (BEI) was obtained, where the data was processed using multiple linear regression analysis. The research results show that partially or simultaneously mobile banking and internet banking and non-performing loans (NPL). has a significant effect on the value of banking companies. This means that the value of mobile banking and internet banking transactions as well as the credit ratio proxied by non-performing loans (NPL) can influence the increase in the value of banking companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022